Epidemiological characteristics and clinical outcomes of primary congenital glaucoma in Xinjiang, China - Xiaokang Wang; Abudusataer Aishan; Xia Li (BMC Ophthalmology, 2026)
Abstract Background Primary congenital glaucoma (PCG) is a rare but sight-threatening disease. However, epidemiological data and long-term outcomes of PCG in Xinjiang are lacking. This study aimed to describe the characteristics, epidemiology, treatment, and outcomes of PCG in Xinjiang, China. Methods The study period spanned from January 2003 to December 2024. The study was conducted in two distinct parts: first, an incidence analysis that compiled case data of all PCG patients treated at designated hospitals in Urumqi, Xinjiang Uygur Autonomous Region; second, a retrospective analysis of clinical characteristics focusing on PCG patients admitted to the glaucoma ward of Xinjiang 474 Hospital during the same period. Results The incidence of PCG was 1 in 20,160 live births (5.0 cases per 100,000). The incidence rate among males was 5.5 per 100,000 live births, while that among females was 4.4 per 100,000 (male relative risk = 1.2). A total of 244 patients with PCG were analyzed, including 144 males (59.0%) and 100 females (41.0%). The median age at presentation was 38.00 months. The infantile type was the most common; the most frequent signs and symptoms were buphthalmos and photophobia with tearing. Trabeculectomy and Trabeculectomy combined with trabeculotomy were the most common surgical procedures. Age at onset was positively correlated with axial length and negatively correlated with visual acuity; patients with delayed presentation had longer axial lengths and poorer visual acuity. Intraocular pressure (IOP) was well-controlled at the final follow-up, and the reoperation rate was 13.9%. Conclusion The incidence of PCG in Xinjiang is comparable to international levels, with a high proportion of male and Uyghur patients, and delayed presentation is common. Significant differences were observed across age groups at onset: individuals with earlier onset had higher IOP and more severe visual impairment. Timely diagnosis and combined surgical procedures can effectively control IOP; early screening and standardized intervention are key to improving the prognosis of PCG and reducing blindness.